Practices, strategies, and challenges in antibiotic treatment and prevention of antimicrobial resistance from the perspectives of Romanian community pharmacists and general practitioners: a Goffman-inspired qualitative interview study - Balea, Lavinia Bianca; Glasdam, Stinne (Frontiers in Antibiotics, 2024)
Introduction Antimicrobial resistance (AMR) represents a persistent and ascensive global threat influenced by antibiotic misuse and overuse. In the Romanian context, patterns of antibiotic consumption and resistance within the healthcare system are marked in the red scenario on the European map. General practitioners and pharmacists, among others, play a major role in stewardship towards AMR. Aim To explore the practices, strategies, and challenges in antibiotic treatment and prevention of antimicrobial resistance from the perspectives of Romanian community pharmacists and general practitioners. Method and Materials Semi-structured interviews were conducted with six general practitioners and five community pharmacists in Romania from January to March 2024. An inductive, Goffman theory-inspired thematic analysis was conducted, inspired by Braun and Clarke’s thematic analysis method, consisting of familiarization with the data, iterative coding guided by theoretically inspired questions, and identification and refinement of (sub)themes. Goffman’s theory of social interaction, focusing on the concepts of front stage, backstage, and roles, guided the analytical questions. Results The results were presented in three overarching themes: ‘Knowledge acquired backstage to support challenges and performance on front stage’, ‘Adapting roles and performances on the front stage: A mix of structured and twisted acts’, and ‘Interprofessional Collaboration: A latent part in the play’s roles and performances’. Professionals prepared their understandings of AMR and antibiotics backstage, with an awareness of the challenges rooted in the Romanian context. The front stage scenario evolved from structured antibiotic performances led by AMR strategies with compliant actors to challenging performances influenced by actors which changed the course of performances and intended AMR strategies. The revealed competition between general practitioners and pharmacists further complicated antibiotic use and AMR-related performances. Conclusion The Romanian socio-political system influenced the course of antibiotic treatment and the professionals’ intended antibiotic related practices and AMR strategies. The study showed a theory-practice gap in health professionals’ practices, leading to limited strategy integration towards AMR and increased antibiotic use. The study underscores the need for context-specific policies and interventions to minimize identified gaps.